Low skeletal muscle mass and postoperative morbidity in surgical oncology: a systematic review and meta‐analysis. Issue 3 (3rd March 2020) - Weerink, Linda B.M.; van der Hoorn, Anouk; van Leeuwen, Barbara L.; de Bock, Geertruida H.
Abstract: Background: Sarcopenia might function as an indicator for frailty, and as such as a risk factor for the development of postoperative complications. The aim of this study was to meta‐analyse the relation between preoperative sarcopenia and the development of severe postoperative complications in patients undergoing oncological surgery. Methods: PubMed and Embase databases were systematically searched from inception until May 2018. Included were studies reporting on the incidence of severe postoperative complications and radiologically determined preoperative sarcopenia. Studies reporting the skeletal muscle as a continuous variable only were excluded. Data were extracted independently by two reviewers. Random effect meta‐analyses were applied to estimate the pooled odds ratio (OR) with 95% confidence intervals (95% CI) for severe postoperative complications, defined as Clavien‐Dindo grade ≥3, including 30‐day mortality. Heterogeneity was evaluated with I 2 testing. Analyses were performed overall and stratified by measurement method, tumour location and publication date. Results: A total of 1924 citations were identified, and 53 studies (14 295 patients) were included in the meta‐analysis. When measuring the total skeletal muscle area, 43% of the patients were sarcopenic, versus 33% when measuring the psoas area. Severe postoperative complications were present in 20%, and 30‐day mortality was 3%. Preoperative sarcopenia was associated with an increased risk of severe postoperative complications (ORpooled : 1.44, 95% CI: 1.24–16.8, P <0.001, I 2 =55%) and 30‐day mortality (ORpooled : 2.15, 95% CI: 1.46–3.17, P <0.001, I 2 =14%). A low psoas mass was a stronger predictor for severe postoperative complications compared with a low total skeletal muscle mass (ORpooled : 2.06, 95% CI: 1.37–3.09, ORpooled : 1.32, 95% CI: 1.14–1.53, respectively) and 30‐day mortality [ORpooled : 6.17 (95% CI: 2.71–14.08, ORpooled : 1.80 (95% CI: 1.24–2.62), respectively]. The effect was independent of tumour location and publication date. Conclusions: The presence of low psoas mass prior to surgery, as an indicator for sarcopenia, is a common phenomenon and is a strong predictor for the development of postoperative complications. The presence of low total skeletal muscle mass, which is even more frequent, is a less informative predictor for postoperative complications and 30‐day mortality. The low heterogeneity indicates that the finding is consistent over studies. Nevertheless, the value of sarcopenia relative to other assessments such as frailty screening is not clear. Research is needed in order to determine the place of sarcopenia in future preoperative risk stratification.